THE UNITED NATIONS AND THE MANAGEMENT OF LIBERIAN REFUGEES IN WEST AFRICA, 1990-2007: A DISCOURSE - OLUSESAN ADEWUNMI OSUNKOYA (International Studies Journal, 2025)
The main aim of this paper is to critically interrogate the nexus between the United Nations (UN) and the management of Liberian refugees in West Africa between 1990 and 2007. The UN has the mandate to provide humanitarian assistance to the various categories of uprooted persons such as refugees, internally displaced persons and asylum seekers. This assistance is being carried out by the UN refugee agency, known as, the United Nations High Commissioner for Refugees (UNHCR). The outbreak of Liberian civil war in 1989 resulted in the production of refugees, who sought safety in the neighbouring countries in West Africa and beyond. By 1990, the UNHCR took over the responsibility of the management of Liberian refugees in their various host countries in West Africa. The various host countries of Liberian refugees in West Africa included Guinea, Sierra Leone, Cote d’ Ivoire, Ghana and Nigeria. Through effective collaboration with the governments of host countries, other UN agencies and non-governmental organisations, the UNHCR succeeded in managing Liberian refugees in these countries. It highlights and discusses major pragmatic steps taken by the UNHCR in conjunction with these partners towards the management of Liberian refugees during this period.  Following the restoration of peace into Liberia in 2003, the UNHCR began to implement durable solutions, which were completed in 2007. Thus, in 2007, the UNHCR finally wounded up the various Liberian refugee camps in West Africa. The methodology adopted in this paper is historical, thematic, qualitative and quantitative utilising materials from both primary and secondary sources of data collection.